Cinema Fans and Fandom Communities vis-a-vis Social Media Platforms (Journal of Advanced Research in Journalism & Mass Communication, 2020)
Social media is considerably a promising platform these days to communicate with people around the world. Cinema over past two decades has also seen drastic changes in terms of content, distribution, exhibition and presentation. Viewers are not dependent on the trailers and teasers being telecasted on television. The scope of getting information and entertainment has widened with digitalization. The cinema viewer shows very peculiar characteristics in relation to view and experience cinema from time to time. At one point the spectator needs to read and analyses the movie review and then decide accordingly whether to watch a film or not. But on the other hand, frequent posts and tweets on social networking sites when watched by the cinema viewer can change the mind and choice for viewing the movie. Cinema lovers and fans go beyond expectationswhile appreciating their star. They do various activities to show their love and respect for the star. Sometimes these activities reach to the masses and in turn help in acquiring the desirable social status for the star. The present research has explored the activities of various fans and clubs of superstar Rajinikanth. Two Facebook pages are taken for the study for the period of six months. The methodology of the study is content analysis where parameters for the analysis of the pages have considered. The researcher also tries to explore the activities of the cinema fans and their behavior while showing love for their star. How to cite this article: Kaur M. Cinema Fans and Fandom Communities vis-a-vis Social Media Platforms. J Adv Res Jrnl Mass Comm 2019; 6(3): 14-19. DOI: https://doi.org/10.24321/2395.3810.201906